The cellist ebook A novel. - Silva, Daniel (Gabriel Allon, 2021)
#1 New York Times Bestseller "The pace of "The Cellist" never slackens as its action volleys from Zurich to Tel Aviv to Paris and beyond. Mr. Silva tells his story with zest, wit and superb timing, and he engineers enough surprises to startle even the most attentive reader."—Wall Street Journal From Daniel Silva, the internationally acclaimed #1 New York Times bestselling author, comes a timely and explosive new thriller featuring art restorer and legendary spy Gabriel Allon. Viktor Orlov had a longstanding appointment with death. Once Russia's richest man, he now resides in splendid exile in London, where he has waged a tireless crusade against the authoritarian kleptocrats who have seized control of the Kremlin. His mansion in Chelsea's exclusive Cheyne Walk is one of the most heavily protected private dwellings in London. Yet somehow, on a rainy summer evening, in the midst of a global pandemic, Russia's vengeful president finally manages to cross Orlov's name off his kill list. Before him was the receiver from his landline telephone, a half-drunk glass of red wine, and a stack of documents.... The documents are contaminated with a deadly nerve agent. The Metropolitan Police determine that they were delivered to Orlov's home by one of his employees, a prominent investigative reporter from the anti-Kremlin Moskovskaya Gazeta. And when the reporter slips from London hours after the killing, MI6 concludes she is a Moscow Center assassin who has cunningly penetrated Orlov's formidable defenses. But Gabriel Allon, who owes his very life to Viktor Orlov, believes his friends in British intelligence are dangerously mistaken. His desperate search for the truth will take him from London to Amsterdam and eventually to Geneva, where a private intelligence service controlled by a childhood friend of the Russian president is using KGB-style "active measures" to undermine the West from within. Known as the Haydn Group, the unit is plotting an unspeakable act of violence that will plunge an already divided America into chaos and leave Russia unchallenged. Only Gabriel Allon, with the help of a brilliant young woman employed by the world's dirtiest bank, can stop it. Elegant and sophisticated, provocative and daring, The Cellist explores one of the preeminent threats facing the West today—the corrupting influence of dirty money wielded by a revanchist and reckless Russia. It is at once a novel of hope and a stark warning about the fragile state of democracy. And it proves once again why Daniel Silva is regarded as his generation's finest writer of suspense and international intrigue.